1995
DOI: 10.1063/1.359511
|View full text |Cite
|
Sign up to set email alerts
|

Shift and deformation of the hysteresis curve of ferroelectrics by defects: An electrostatic model

Abstract: Lattice cells containing point defects in ferroelectric single crystals can behave as a second phase. In addition to the role these defects have in the variation of several chemical and physical properties of the ferroelectric, they modify those physical properties of the ferroelectric that are manifested in the hysteresis curve. These effects are: the shearing of the loop by all kinds of defects, the shifting of the hysteresis curve along the field axis (internal bias) by oriented polar defects, and the chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
51
0
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(54 citation statements)
references
References 10 publications
0
51
0
3
Order By: Relevance
“…[1][2][3][4] Other explanations included domain pinning, 5,6 rectifying effects formed at the ferroelectric-electrode interface [7][8][9] and the effect of passive layers. [10][11][12] It seems that the definitive mechanism is still not fully understood and the voltage shift may arise from multiple sources. Theoretical models to gain deeper insight using different approaches have been proposed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] Other explanations included domain pinning, 5,6 rectifying effects formed at the ferroelectric-electrode interface [7][8][9] and the effect of passive layers. [10][11][12] It seems that the definitive mechanism is still not fully understood and the voltage shift may arise from multiple sources. Theoretical models to gain deeper insight using different approaches have been proposed.…”
mentioning
confidence: 99%
“…A most notable phenomenon is the large voltage offset along the horizontal ͑electric field͒ axis found in the hysteresis loop measurements. [1][2][3][4][5][6][7][8][9][10][11] The result is a deformed hysteresis loop with asymmetric switching. 6 Many researchers attributed the shift effect to the internal field caused by trapped charge carriers.…”
mentioning
confidence: 99%
“…[1][2][3][4] Other explanations included domain pinning, 5,6 rectifying effects formed at the ferroelectric-electrode interface, [7][8][9] and the effect of passive layers. [10][11][12] It seems that there is no general agreement on a definitive mechanism and that the voltage shift may possibly arise from multiple sources. In addition, many previously suggested mechanisms have not been fully examined by accurate physical models or simulations.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most notable phenomenon is the large voltage offset along the horizontal (electric-field) axis found in the hysteresis loop measurements. [1][2][3][4][5][6][7][8][9][10][11] The result is a deformed hysteresis loop with asymmetric switching. 6 Many researchers attributed the shift effect to the internal field caused by trapped charge carriers.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments have shown that the coercive field is larger while the remanent polarization is lower in the presence of defects or damage vacancies are present. [22][23][24][25][26][27] On the other hand, due to the interaction between the electrode and the film, interfacial stress is always present at the surface. This stress might be induced by thermal-mismatch or lattice mismatch.…”
Section: ͑10͒mentioning
confidence: 99%